The udhA Gene of Escherichia coli Encodes a Soluble Pyridine Nucleotide Transhydrogenase - Boonstra, Birgitte (American Society for Microbiology, 1999)
The udhA gene of Escherichia coli was cloned and expressed in E. coli and found to encode an enzyme with soluble pyridine nucleotide transhydrogenase activity. The N-terminal end of the enzyme contains the fingerprint motif of a dinucleotide binding domain, not present in published E. coli genome sequences due to a sequencing error. E. coli is hereby the first organism reported to possess both a soluble and a membrane-bound pyridine nucleotide transhydrogenase.